Mobile phone deception in Nigerian: deceivers' skills, truth bias or respondents' greed? (2012)
"The use of mobile phones to deceive and defraud in Nigeria has received widespread comments and complaints but not empirical investigations. Guided by Buller and Burgoon’s interpersonal deception theory, this article examined the strategies employed by deceivers, the dimension of lies told and why mobile phone deception works among Nigerians. This it did through interviews with victims and near-victims of deception, focus group discussions with users, and participant observation. Mobile phone deception falls into two broad categories: impression-related deception and deception for monetary fraud. The strategies employed by mobile phone deceivers are the same as those employed in face-to-face deception. Mobile phone deception in Nigeria succeeds widely not so much as a result of poverty, greed or truth bias. The success of mobile phone deception is largely the result of deceivers’ skills, the overall mobile phone environment in Nigeria and certain socio-cultural characteristics of Nigerians. Studies of mobile telephony should be driven by perspectives that take socio-cultural milieu into consideration. "